Dysbiosis and predicted function of dental and ruminal microbiome associated with bovine periodontitis - Borsanelli, Ana C.; Athayde, Flávia R. F.; Riggio, Marcello P.; Brandt, Bernd W.; Rocha, Fernando I.; Jesus, Ederson C.; Gaetti-Jardim, Elerson; Schweitzer, Christiane M.; Dutra, Iveraldo S. (Frontiers in Microbiology, 2022)
Extensive cattle livestock is advancing in Amazonia and its low productivity, with consequent pressure to open new areas, is partly due to sanitary problems and, among them, the periodontal diseases, whose environmental triggers or modifying factors are unknown. In this study, we used high-throughput sequencing, network analysis and predicted functions to investigate the dental and ruminal microbiota of cattle raised in new livestock areas in the Amazon and identify possible keystone pathogens and proteins associated with the disease. Ninety-three genera were common in dental and ruminal fluid microbiomes and among them periodontal pathogens such as Fusobacterium, Prevotella, Porphyromonas and Actinomyces were recognized. Network analysis showed that dental microbiomes of clinically healthy animals tend to comprise a group of OTUs in homeostasis and when analyzed together, dental and ruminal fluid microbiomes of animals with periodontitis had almost twice the number of negative edges, indicating possible competition between bacteria and dysbiosis. The incisor dental and ruminal fluid microbiomes were dominated by a core community composed of members of the phyla Firmicutes and Bacteroidetes. Network results showed that members of the Prevotella genus stood out among the top five OTUs, with the largest number of hubs in the dental and ruminal microbiota of animals with periodontitis. Protein families linked to an inflammatory environment were predicted in the dental and ruminal microbiota of cattle with periodontitis. The dissimilarity between dental microbiomes, discriminating between healthy cattle and those with periodontitis and the identification of possible key pathogens, represent an important reference to elucidate the triggers involved in the etiopathogenesis of bovine periodontitis, and possibly in the development of measures to control the disease and reduce the pressures for deforestation.